Carrying them with us : living through pregnancy or infant loss - Engelstad, David, 1954-; Malotky, Catherine, 1954- (Living With Hope., 2019)
Carrying Them with Us: Living through Pregnancy and Infant Loss is a reflection on what pastors David Engelstad and Catherine Malotky have learned since the day in 1984 when their eight-week-old daughter Erin died of Sudden Infant Death Syndrome. Drawing on their own loss, they offer themselves as companions to parents who struggle to deal with the end of an eagerly anticipated pregnancy or the death of a joyfully welcomed baby. Readers will find in Carrying Them with Us comfort and wisdom, a spiritual perspective, and practical guidance. The authors also invite into this journey the caregivers--family, clergy and medical professionals, and friends--who accompany grieving parents. The book is organized around five questions the authors have found central to many parents' unfolding story: (1) How can this have happened? (2) Why do I feel like this? (3) How do I keep going? (4) What do I make of life after this? And (5) Who am I becoming? Engelstad and Malotky show readers a path from devastating sadness toward healing, a way for grieving parents to keep going and, one day, to embrace new life.